Self-Acceptance for Students Through Reality Counseling Containing Local Wisdom - Rita Kartika Sari; Musyarrafah Sulaiman Kurdi; Muqarranah Sulaiman Kurdi; Eunike Rose Mita Lukiani; Pandu Adi Cakranegara (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research aims to analyze the effectiveness of reality counseling containing local wisdom in increasing students' self-acceptance. The research method used is quantitative. The sample in this study was 33 students in class VII.1 of junior high school. The data collection method uses a questionnaire. Then, the data was analyzed using the Mann-Whitney test (U-test). The results of the research found that the average student's self-acceptance score before being given the Reality Counseling intervention with Local Wisdom Content (pretest) was 138.1. Then the average student self-acceptance score after being given the intervention (posttest) was 110.56. There was a decrease in scores before and after the intervention of Reality Counseling activities containing Local Wisdom by 27.54. Then, after being analyzed using the nonparametric statistical test Mann Whitney U Test, the Asymp.Sig (2-tailed) was 0.034. Thus, it can be concluded that Reality Counseling activities containing Local Wisdom have a significant influence in reducing students' low self-acceptance. Reality counseling containing local wisdom can be an alternative in increasing students' self-acceptance so that they become students who are confident, enthusiastic and independent.